Relationship between perceived athletic competence, maturational status and physical activity (Journal of Physical Education (Maringá), 2018)
The Organized Practice of physical activities (OP) is a kind of physical activity carried out in an organized program of frequency and duration, under the supervision of an adult (teacher or coach), and involve some kind of demonstration of performance which may be competitions and/or festivals. This study aimed to investigate the relationship between the Perceived Athletic Competence and the time spent in Organized Practices in sports and dance, considering the adolescent maturational status and sex. In this cross-sectional and correlational study participated 213 boys and girls aged between 13 and 16 years. The Perceived Athletic Competence and the Organized Practices of the individuals was assessed by questionnaires. The maturational status was determined by calculating the peak growth rate. Bivariate and partial correlations were performed.  The results showed that regardless of maturational status of individuals, there was a positive relationship between Perceived Athletic Competence and total Organized Practices for boys and girls (rho=0.40, P